DIFFICULTIES IN DIFFERENTIATED DIAGNOSIS OF LUNG CANCER AND INFLAMMATORY CHANGES IN LUNG TISSUE - Z. V. Grigorievskaya; V. L. Utkina; V. А. Byakhova; I. N. Petukhova; N. S. Bagirova; I. V. Tereshchenko; A. I. Dmitrieva; E. D. Grigorievsky; N. V. Dmitrieva (Сибирский онкологический журнал)
The differential diagnosis of pulmonary diseases is extremely difficult and requires high qualifications of the radiologist and clinician. The differential diagnosis is used to distinguish different lung diseases: nonspecific inflammatory lung diseases (empyema, abscess, pneumonia), tuberculosis, sarcoidosis, benign tumors, lung cancer, lymphogranulomatosis, metastatic changes, and inflammatory changes in lung tissue. We present a clinical case, in which the differential diagnosis between tumor and inflammatory changes in lung tissue allowed the choice of optimal treatment tactics.